Causes and Effects of Loss of Classical Nonhomologous End Joining Pathway in Parasitic Eukaryotes - Nenarokova, Anna; Záhonová, Kristína; Krasilnikova, Marija; Gahura, Ondřej; McCulloch, Richard; Zíková, Alena; Yurchenko, Vyacheslav; Lukeš, Julius (mBio, 2019)
We report frequent losses of components of the classical nonhomologous end joining pathway (C-NHEJ), one of the main eukaryotic tools for end joining repair of DNA double-strand breaks, in several lineages of parasitic protists. Moreover, we have identified a single lineage among trypanosomatid flagellates that has lost Ku70 and Ku80, the core C-NHEJ components, and accumulated numerous insertions in many protein-coding genes. We propose a correlation between these two phenomena and discuss the possible impact of the C-NHEJ loss on genome evolution and transition to the parasitic lifestyle.IMPORTANCE Parasites tend to evolve small and compact genomes, generally endowed with a high mutation rate, compared with those of their free-living relatives. However, the mechanisms by which they achieve these features, independently in unrelated lineages, remain largely unknown. We argue that the loss of the classical nonhomologous end joining pathway components may be one of the crucial steps responsible for characteristic features of parasite genomes.
Keywords: fylogeneze; Phylogeny; parasite; Eukaryota; signální transdukce; DNA repair; Amino Acid Sequence; paraziti; Genomics; Signal Transduction; molekulární modely; antigen Ku; oprava DNA spojením konců; Models, Molecular; genom; Animals; DNA End-Joining Repair; konformace proteinů; Ku Autoantigen; zvířata; sekvence aminokyselin; genome size; Genome; Protein Conformation; Parasites; genomika